Hotel Employee’s Job Satisfaction and its Implication to Turnover Intention - Luh Putu Kristiani; I Gede Mudana; Ni Putu Wiwiek Ary Susyarini; Made Sudiarta (International Journal of Glocal Tourism, 2020)
Purpose: This research is to know how the implementation and the level significance of employees’ job satisfaction on turnover intention at a 5 star resort hotel in the southern part of Bali. Research methods: To solve the problem, the writers use quantitative analysis (simple linear regression analysis) and qualitative analysis with SPSS 25. Based on the results it is known that the employees’ job satisfaction at the hotel is quite satisfied with the aspects of the job satisfaction provided by the management. Findings: In the T-test result sig. value 0.003 < 0.005 means the hotel employess’ job satisfaction gives a significant influence, and has a negative influence on turnover intention through the beta coefficient of (?) -0.200, with r square of 0.080 in coefficient determination means that the level significances or contribution of the employees’ job satisfaction variable affecting the turnover intention by 8% and the remainder by 92% is determined by another variable not described in this research. Implication: The hotel management should provide a promotional opportunity to employees and also improve the others employees’ job satisfaction aspects such as salary, workload, and relationship with supervisor and co-workers.